2012
DOI: 10.1080/03055698.2011.643106
|View full text |Cite
|
Sign up to set email alerts
|

How well elementary teachers identify parallelogram?

Abstract: This report summarises a study examining preservice elementary teachers' geometry content knowledge with a focus on parallelogram. It was a descriptive study examining 45 preservice teachers' reasoning in the process of determining which quadrilateral can be classified as a parallelogram. Findings have revealed that these elementary teachers do not possess sound understanding of parallelogram and class inclusion between parallelogram and trapezoid at the expected level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Alanyazında dörtgenlere ilişkin farklı gruplarla hem yurt dışında hem de ülkemizde birçok araştırma yapılmıştır. Bu araştırmalar ilköğretim ve lise düzeyindeki öğrenciler, sınıf öğretmeni adayları (Duatepe-Paksu, İymen & Pakmak, 2012;Erşen ve Karakuş, 2013;Fujita & Jones, 2006a, 2006bFujita, 2012), matematik öğretmeni adayları (Bütüner ve Filiz, 2016;Pickreign, 2007;Türnüklü ve ark., 2013;Türnüklü 2014;Zaskis & Leikin, 2008) ve öğretmenler (Akkaş & Türnüklü, 2015;Bütüner & Filiz, 2017) ile gerçekleştirilmiştir. Araştırmalar hiyerarşik sınıflandırmayı (Aktaş ve Aktaş, 2012a;Akuysal, 2007;Bütüner ve Filiz, 2016;De Villiers, 1994;Erez & Yerushalmy, 2006;Erşen ve Karakuş, 2013;Fujita, 2008Fujita, , 2012Fujita & Jones, 2007;Monaghan, 2000;Okazaki & Fujita, 2007;Türnüklü, 2014), yamuğu (Doğan, Özkan, Çakır, Baysal ve Gün, 2012;Loc & Viet, 2017;Popovic, 2012), paralelkenarı (Aktaş ve Aktaş, 2012b;Duatepe-Paksu ve ark., 2012;Fujita & Jones, 2006b;Toumasis, 1995;Ulusoy ve Çakıroğlu, 2017), dikdörtgen, kare ve eşkenar dörtgeni (Duatepe-Paksu, 2017;Erez & Yerushalmy, 2006;Pickreign, 2007;Zaskis & Leikin, 2008), dörtgenlere ilişkin kavram imajlarını (Erşen ve Karakuş, 2013;Fujita & Jones,...…”
Section: Introductionunclassified
“…Alanyazında dörtgenlere ilişkin farklı gruplarla hem yurt dışında hem de ülkemizde birçok araştırma yapılmıştır. Bu araştırmalar ilköğretim ve lise düzeyindeki öğrenciler, sınıf öğretmeni adayları (Duatepe-Paksu, İymen & Pakmak, 2012;Erşen ve Karakuş, 2013;Fujita & Jones, 2006a, 2006bFujita, 2012), matematik öğretmeni adayları (Bütüner ve Filiz, 2016;Pickreign, 2007;Türnüklü ve ark., 2013;Türnüklü 2014;Zaskis & Leikin, 2008) ve öğretmenler (Akkaş & Türnüklü, 2015;Bütüner & Filiz, 2017) ile gerçekleştirilmiştir. Araştırmalar hiyerarşik sınıflandırmayı (Aktaş ve Aktaş, 2012a;Akuysal, 2007;Bütüner ve Filiz, 2016;De Villiers, 1994;Erez & Yerushalmy, 2006;Erşen ve Karakuş, 2013;Fujita, 2008Fujita, , 2012Fujita & Jones, 2007;Monaghan, 2000;Okazaki & Fujita, 2007;Türnüklü, 2014), yamuğu (Doğan, Özkan, Çakır, Baysal ve Gün, 2012;Loc & Viet, 2017;Popovic, 2012), paralelkenarı (Aktaş ve Aktaş, 2012b;Duatepe-Paksu ve ark., 2012;Fujita & Jones, 2006b;Toumasis, 1995;Ulusoy ve Çakıroğlu, 2017), dikdörtgen, kare ve eşkenar dörtgeni (Duatepe-Paksu, 2017;Erez & Yerushalmy, 2006;Pickreign, 2007;Zaskis & Leikin, 2008), dörtgenlere ilişkin kavram imajlarını (Erşen ve Karakuş, 2013;Fujita & Jones,...…”
Section: Introductionunclassified
“…Similarly, Ndlovu (2014) reported that 14 of 16 preservice teachers could provide the correct definition of a rectangle and Erşen and Karakuş (2013) observed that 5 of 6 pre-service teachers could do so. Additionally, Duatepe-Paksu et al (2012) found that 10 (22%) of 45 pre-service teachers would erroneously define a rectangle while Brunheira and da Ponte (2015) reported that 22 (39%) of 57 pre-service teachers indicate an erroneous definition. In Turkey, Erdogan and Dur (2014) reported that 39% of 57 pre-service teachers could accurately define a rectangle and Güner and Gülten (2016) observed that only 18 (34%) of 50 pre-service teachers could do this.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while one teacher (3%) included the link between a trapezoid and rectangle in their knowledge map, the trapezoid-parallelogram relation was demonstrated by only 7 teachers (23%). Likewise, Duatepe-Paksu et al (2012) found that 10 (22%) of 45 pre-service teachers erroneously define a trapezoid whereas Ndlovu (2014) observed that 12 (75%) of 16 pre-service teachers could give the correct definition. Moreover, Güner and Gülten (2016) reported that 32 (64%) of 50 pre-service teachers accurately define a trapezoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations